A Novel Internal and External Bypass Method to Safeguard Cerebral Blood Flow During Aortic Arch Endovascular Repair Requiring Triple In Situ Fenestrations. (October 2019) - Wang, Wenwen; Zhang, Xin; Liu, Changjian; Zhu, Yuelin; Yu, Tong; Liu, Chen; Li, Xiaoqiang; Liu, Zhao
Purpose: To report a novel internal and external blood bypass method for cerebral protection during in situ triple-fenestrated stent-graft repair in the aortic arch.Technique: A method was devised to combine internal and external blood bypass circuits to preserve cerebral blood flow when all 3 supra-aortic branches are covered by the stent-graft. Long 14-F to 18-F introducers are placed retrogradely into the right and left common carotid arteries (CCAs). Smaller sheaths are placed antegradely into the internal carotid arteries (ICAs) bilaterally and into the right CCA introducer, which has had an aperture cut into it for flow to pass into the smaller sheath. The right CCA introducer is positioned in the ascending aorta to supply the innominate artery; the smaller sheath in the right CCA introducer is positioned at the aperture. The small sheath in the right CCA is connected to the left ICA sheath, and the left CCA fenestration is made and stented. The left ICA sheath is connected to the right ICA sheath, and the right CCA introducer is pulled back to the origin of the innominate artery and the smaller sheath removed. The fenestrations for the innominate and left subclavian arteries are opened sequentially. In 8 patients, complete bypass to maintain brain perfusion was performed for an average 17.6±6.9 minutes; intraoperative transcranial Doppler monitoring during flow bypass showed no notable decline in intracranial blood flow velocity. Two patients suffered stroke; one recovered completely.Conclusion: A cerebral protection strategy that integrates internal and external blood flow bypass techniques to maintain adequate brain blood flow is simple and feasible for in situ triple-fenestration aortic arch stent-graft repairs. However, neurological complications were not avoided with this method; thus, further research and development are required.